Re-designing the Mozambique vaccine supply chain to improve access to vaccines. Issue 41 (22nd September 2016) - Lee, Bruce Y.; Haidari, Leila A.; Prosser, Wendy; Connor, Diana L.; Bechtel, Ruth; Dipuve, Amelia; Kassim, Hidayat; Khanlawia, Balbina; Brown, Shawn T.
Highlights: Populations and vaccine regimens have grown since many supply chains were designed. Adding new vaccines may exacerbate bottlenecks, inhibiting the flow of all vaccines. Our team implemented a supply chain evaluation and redesign process in Mozambique. The process integrated HERMES computational modeling with on-the-ground implementers. Redesign improved Mozambique's vaccine supply chain efficacy and efficiency. Abstract: Introduction: Populations and routine childhood vaccine regimens have changed substantially since supply chains were designed in the 1980s, and introducing new vaccines during the "Decade of Vaccine" may exacerbate existing bottlenecks, further inhibiting the flow of all vaccines. Methods: Working with the Mozambique Ministry of Health, our team implemented a new process that integrated HERMES computational simulation modeling and on-the-ground implementers to evaluate and improve the Mozambique vaccine supply chain using a system-re-design that integrated new supply chain structures, information technology, equipment, personnel, and policies. Results: The alternative system design raised vaccine availability (from 66% to 93% in Gaza; from 76% to 84% in Cabo Delgado) and reduced the logistics cost per dose administered (from $0.53 to $0.32 in Gaza; from $0.38 to $0.24 in Cabo Delgado) as compared to the multi-tiered system under the current EPI. The alternative system also produced higher availability at lower costs after new vaccine introductions. Since reviewing scenarios modeling deliveries every two months in the north of Gaza, the provincial directorate has decided to pilot this approach diverging from decades of policies dictating monthly deliveries. Discussion: Re-design improved not only supply chain efficacy but also efficiency, important since resources to deliver vaccines are limited. The Mozambique experience and process can serve as a model for other countries during the Decade of Vaccines. For the Decade of Vaccines, getting vaccines at affordable prices to the market is not enough. Vaccines must reach the population to be successful.